Isolation of Protoplasts from Nepenthes - A Plant Carnivore (Plant Tissue Culture and Biotechnology, 2014)
Protoplasts were isolated from the lamina of greenhouse grown Nepenthes ampullaria and the hybrid N. Rokko Exotica in order to develop a protocol for protoplast isolation suitable for wild species of Nepenthes. Various molarities utilizing mannitol or sorbitol and different enzyme mixtures and concentrations as well as incubation times were evaluated to maximize protoplast yield and viability.  The most effective treatment, a 4 hrs incubation at 40 rpm and 25°C in a solution consisting of 0.5 M sorbitol, 5% cellulase Onozuka R-10, 0.5% macerozyme R-10, and 0.3% pectolyase Y-23, generated 4.35 × 106 protoplasts/ gfw of which 62.1% were viable.  Culture was attempted in respect of  regeneration of the cell wall, however, no cell division was observed. Plant Tissue Cult. & Biotech. 24(1): 93-100, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19217